DETERMINAN PERILAKU IBU HAMIL DALAM MENGIKUTI KELAS IBU HAMIL DI WILAYAH KERJA PUSKESMAS LANGSAT PEKANBARU TAHUN 2020: DETERMINANT PREGNANT WOMAN BEHAVIOR IN FOLLOWING PREGNANT WOMEN CLASSES IN THE PUSKESMAS LANGSAT WORK AREAS IN 2020 - Nurhayati Nur; Risa Amalia; Alhidayati Alhidayati (Progam Studi Kesehatan Masyarakat STIKes Hang Tuah Pekanbaru, 2021)
Based on data from the Pekanbaru City Health Office in 2019, the number of pregnant women was 170,366 people, of which 21 Pekanbaru City Puskesmas who had implemented classes for pregnant women were 92.41%. Data from the Pekanbaru City Health Office from 3 Puskesmas with the lowest in the implementation of the class of pregnant women that have not been going well are at Langsat Puskesmas, namely 7.7% with 3 classes of pregnant women. This study aims to determine the determinants of pregnant women behavior in following classes of pregnant women in the Langsat Pekanbaru Public Health Center in 2020. This type of research is quantitative with a cross sectional design. The study population was all pregnant women in the Langsat Pekanbaru Health Center with a total of 580 people and the research sample was 86 people. The sampling technique was purposive sampling. Data analysis was performed univariate and bivariate with the chi-square test (? = 0.05). The results of the bivariate analysis showed that there was a significant relationship between perception (? = 0.017 ?? = 0.05), education (? = 0.018 ?? = 0.05), knowledge (? = 0.024 ?? = 0.05), attitude ( ? = 0.006 ?? = 0.05), parity (? = 0.030 ?? = 0.05), information media (? = 0.012 ?? = 0.05), family support (? = 0.012 ?? = 0.05) ), and the role of health workers (? = 0.002 <? = 0.05) with the behavior of pregnant women. Based on the results of the research, the conclusion is that there is a relationship between perception, education, knowledge, attitudes, parity, information media, family support, the role of health workers and the behavior of pregnant women in attending classes for pregnant women. So suggestions for high-risk pregnant women to be more active in participating in the class program for pregnant women and for health workers need to increase outreach to mothers about the importance of joining pregnant women classes. In addition, support from husbands is needed to increase maternal visits in the class of pregnant women.